2021
DOI: 10.1007/s11213-021-09577-6
|View full text |Cite
|
Sign up to set email alerts
|

The Other Side of Success Factors—A Systemic Methodology for Exploring Critical Success Factors

Abstract: This paper puts forward a systemic methodology to explore Critical Success Factors (CSFs). The common idea about ranking CSFs is to explore the relationship of 'more important', i.e. directly assessing whether success factor A is more important than factor B. This idea is prominent in the prevailing approaches, e.g. the qualitative inquiry, quantitative analysis, and multi-criteria decision making. Exploring CSFs from a different lens, this paper argues for systemic approaches, reckoning that manifold interrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…(5) In dimension "C5", "Strategic deployment (C51)" is the most important evaluation criterion. Daniel (1961) argues that most companies have two to six factors that determine their success (Tuan, 2021), if a company wants to be successful, it must strive for excellence in these factors. We assume that the weight of the key assessment criteria must be greater than the average weight of all assessment criteria (1/15 or 0.0667) to be selected as a meaningful key indicator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) In dimension "C5", "Strategic deployment (C51)" is the most important evaluation criterion. Daniel (1961) argues that most companies have two to six factors that determine their success (Tuan, 2021), if a company wants to be successful, it must strive for excellence in these factors. We assume that the weight of the key assessment criteria must be greater than the average weight of all assessment criteria (1/15 or 0.0667) to be selected as a meaningful key indicator.…”
Section: Resultsmentioning
confidence: 99%
“…If a company is to be successful, it must do a particularly good job with these factors (Tuan, 2021). In the AHP study, among the eight key criteria, the first two indicators, Strategic Planning and Strategic Deployment have a weighting of nearly 0.1 and above, indicating that the first two are particularly important in the decision to grow free cash flow.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/app14031017/s1. References [10,24,30,31,[44][45][46][47][48][49][50][51] are cited in Supplementary Materials part.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…They are endangering the organization's core activity because of a low and challenging understanding of the benefits of a new ERP software, and Hong et al [12], also highlighted an unusually high failure rate. Numerous studies [13][14][15][16][17][18][19] have demonstrated that measuring implementation success can involve both business and project success. The success of an ERP project implementation is measured by whether the ERP system is delivered on time, on budget, and meets the specified goal.…”
Section: Introductionmentioning
confidence: 99%
“…CSFs are pivotal factors or areas in business that, when executed exceptionally well, empower an organization to achieve success and prosperity. These factors constitute critical elements essential for outstanding organizational performance in reaching its goals [16][17][18]. However, concerning CSFs in IT implementation, Rockart [19] pioneered a research method explicitly designed to elicit CSFs.…”
Section: Introductionmentioning
confidence: 99%